The effectiveness of awareness education among adolescent inhalant addicts - Coşkun, Sibel; Işıl, Özlem; Ögel, Kültegin (Journal of Dependence, 2008)
Objective: In the study, the aim was training education about addiction, effects of inhalants, and coping with desire of substance use to inhalant users from Istanbul Bakırköy Inhalant Use Research and Treatment Center (UMATEM) in order to obtain awareness and to increase the cooperation in treatment. Method: “YENİDEN-Association of Health and Education” prepared topics for three individual sessions as a book “A psychosocial guidebook for children living at streets and using substances”. Experiment group consisted of 31 adolescents, and experiment group’s level of knowledge was compared with control group. Results: Adolescents’ level of socioeconomic status did not differ from each other. Questionnaires for pre-, post- and after a week were assessed their knowledge according to their right answers. The difference between experiment group and control group -related to the knowledge and motivation for treatment- was statistically significant (p<.001). Experiment group adolescents’ inhalant use was found less than the control group adolescents’ after one year of treatment, and this difference was statistically significant (p<.01). Conclusions: The awareness education made a contribution in increasing experiment group adolescents’ level of knowledge and motivation. Applying similar education and skill development programs more frequently and widespread is very significant.